A new paradigm for R&D in water resources engineering - Chetan Pandit (Irrigation and Drainage, 2003)
The technology in water resources engineering (WRE) seems to be stagnant. No new technology of any significance has emerged for quite some time now and there seems to be none in the pipeline. In the WRE sector, R&D does not generate the same level of excitement and challenges that it does in other sectors. Shortage of funds does not seem to be the reason for this disappointing performance of R&D. The main problems are: WRE R&D has very little potential for patents, Intellectual Property Rights (IPR) and profit and therefore the private sector does not take any interest in R&D in WRE. Most of the research pursued by the universities is too theoretical. There is very little applied research. There is a marked lack of creativity and inspiring ideas for R&D. There are neither any “technology dreamers” nor any dreams. Users are not being involved in the planning. The time is running out for R&D managers in WRE. The vision plans of most governments incorporate a set of measurable performance targets to be achieved in a stipulated time frame. Many of the targets are less than 10 years away. Therefore, if R&D is to be of any assistance in achieving the targets set for 2010, then that R&D must start now, not next year. The present approach to R&D has not produced desired results and, therefore, it must be changed immediately. The paper proposes a new approach to provide an impetus to R&D in the WRE sector. Copyright © 2003 John Wiley & Sons, Ltd.